ACCESSING SOCIAL ENTREPRENEURIAL RESOURCES: EVIDENCE FROM TERENGGANU, MALAYSIA - Mohd Said, Nur Syifaa Athirah; Ab Ghani, Nur Izzati; Nasir, Muhamad Nasyat Muhamad; Roslan, Farah; Mohd Nor, Zanariah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
In this study, an instrument to measure entrepreneurial resources was examined to analyse the social entrepreneurship readiness of youth entrepreneurs in Terengganu. This study thus obtained seventeen items related to entrepreneurial resources from previous studies and different industries, and these were revised according to the social entrepreneurship readiness industry. Experts validated the items, and a pilot study was then conducted with 100 randomly selected youth entrepreneurs in Terengganu who registered with the Companies Commission of Malaysia SSM as participants for this study. Three dimensions (Financial Resources, Government Support, and Human Capital) were established by Exploratory Factor Analysis (EFA), and internal reliability was confirmed for each dimension. In addition to providing empirical evidence, this study contributes methodologically by developing and validating a new instrument that can be used in assessing entrepreneurial resources in the social entrepreneurship domain. This instrument not only strengthens the understanding of entrepreneurial resources as a construct but also offers a practical tool for policymakers, educators, and researchers to assess youth readiness in driving social entrepreneurship initiatives in Malaysia and beyond.